Di- and trinuclear sandwich complexes of a cross-conjugated fulvene. Issue 6 (18th January 2023) - Kudo, Eiji; Oba, Yuki; Yamamoto, Koji; Murahashi, Tetsuro
Abstract : We report di- and trinuclear sandwich complexes of cross-π-conjugated fulvenes. The reversible extrusion of a Pd atom from inside to outside the sandwich framework occurs due to the cross-π-conjugation of fulvene. Abstract : We report di- and trinuclear palladium sandwich complexes of cross-π-conjugated fulvenes. Structural and theoretical analysis revealed that a fulvene sandwich framework holds a metal–metal bonded moiety, where the dinuclear and trinuclear bonds feature strong donation and back-donation, respectively. The trinuclear fulvene sandwich complex undergoes a unique reversible extrusion of a Pd atom from inside to outside the sandwich framework.